(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
this article discusses the basics of ball-carrying techniques and tactics in the game of football that are important to practitioners and should be widely used in practice, as well as the social and biological aspects of the process of training athletes in the principles of interaction.